Mapping of the functional determinants of the integrin beta 1 cytoplasmic domain by site-directed mutagenesis. - Marcantonio, E E (1990)
We describe here the expression of deletion mutants of the cytoplasmic domain of the avian integrin beta 1 subunit. These mutants, which contain termination codons at positions 767, 776, 791, and 800, were transfected into mouse 3T3 cells to determine which sequences were essential for localization of integrins into focal contact sites. In all cases, high-level expression of the truncated avian integrins was obtained. Heterodimers were formed between the exogenous truncated avian beta 1 subunits and endogenous mouse alpha subunits, and these heterodimers were efficiently exported to the cell surface. The longest truncated beta 1 subunit tested, which is only four amino acids shorter than the wild type, does localize to focal contacts. In contrast, beta 1 subunits with moderately long truncations of the cytoplasmic domain failed to localize to focal contacts, including one which contains the consensus sequence for tyrosine phosphorylation. Surprisingly, a mutant subunit in which the bulk of the cytoplasmic domain was missing (but the segment nearest the membrane including the dibasic residues (RR) remained) did localize weakly to focal contacts. These results implicate the peptide segment nearest to the transmembrane region in focal contact localization. In addition, mutant subunits that included this segment together with a larger portion of the cytoplasmic domain did not localize as well as the shorter form, suggesting that these cytoplasmic domain segments are defective, presumably because of abnormal folding.